Math, asked by paru1905, 1 year ago

prove that
cosecA (1+cosA) (cosecA-cotA)=1​

Answers

Answered by vyshnavi9
1

Step-by-step explanation:

Hope this will help u..☺

And sorry for a mistake in this answer.

Attachments:
Answered by princess8189
3

Step-by-step explanation:

lhs=cosecA(1+cosA)(cosecA-cot A)

=1/sinA(1+cosA)(1/sinA-cosA/sinA)

=1+cosA/sinA(1-cosA/sinA)

=by using identity (a+b)(a-b)

=1-cos^A /sin^A

=now by using identity sin^A +

cos^A =1

=sin^ A /sin^A

=1

=rhs

Similar questions